The Effect of Coffee Consumption on Acute Increased Blood Pressure in Normotensive Teens - Eunike Jennifer Tandiono; Ecie Budiyanti (Journal of Urban Health Research, 2023)
Introduction: Caffeine has been known to elevate blood pressure. However, the effect of drinking coffee on blood pressure varied among studies. This study examines the impact of coffee on the acute response of blood pressure in a late adolescent with normal blood pressure. Method: This cross-sectional study with a cross-over design involving 16 male and late female adolescents. The intervention group subjects drank a glass of 200 ml of Robusta coffee (commercial brand), while the control group drank plain water. After a 7-day washout, the intervention group became the control group and vice versa. A paired t-test was applied to evaluate systolic blood pressure (SBP) and diastolic blood pressure (DBP) before and after the intervention. The significance was set at p<0.05. Results: SBP and DBP in the control group were unchanged (Δ0.8 and 0.6 mmHg, p=0.237 and 0.584, respectively). SBP and DBP in the intervention group were significantly elevated (Δ8.4 and 8.1 mmHg, p<0.01 and <0.01, respectively). Discussion: Our findings demonstrated that coffee increases SBP and DBP significantly in the late adolescent with normal BP. Increased sympathetic tones and blocking adenosine receptors are suggested to increase BP. However, some limitations were also found, so the results should be interpreted carefully. Conclusion: A 200 ml coffee (Robusta) increased SBP and DBP in late adolescents with normal blood pressure.   Keywords: Caffeine - Blood Pressure - Sympathetic Activity - Adenosine Receptor - Phosphodiesterase